Assay of Serum Iron and TIBC: A Preliminary Study for Survey Shortlisting Suspected Tuberculosis Patients - Dipak Kumar Chattopadhyay (Indian Journal of Medical Biochemistry)
Aim: Mycobacterium tuberculosis (Mtb) growing within the phagosome of macrophases secretes siderophores, a small molecule having a high affinity for Fe+3 iron, to take up iron-loaded mycobactin (MBT) and carboxymycobactin (CMBT) from the environment to meet its iron (Fe) need. Mycobacterium tuberculosis is well capable to utilize Fe from heme and hemoglobin by the secretion of heme-binding protein, cell surface proteins, etc., by the mycobacteria. On the other hand, the measurement of serum total iron binding capacity (TIBC) denoting the maximum amount of Fe carried by transferrin (Tf) present in serum entails indirectly a measure of serum Tf level. The index author has interpreted the serum iron and serum TIBC level and the ratio of serum iron and serum TIBC as a preliminary survey to shortlist the suspected population deserving confirmatory test for tuberculosis (TB). This is to categorically declare that assay of these parameters is not to be used as TB diagnostic but only for shortlisting suspected TB patients from the general population. Materials and methods: The study was conducted on total of 180 participants divided into 3 groups: Group I - normal control (n = 45); Group II - lung disease control (n = 45); and Group III - patients suffering from TB (3A: Pulmonary TB (n = 45) and 3B: Extrapulmonary TB (n = 45)). Serum Fe and TIBC levels were measured for all participants and also for group III and group II subjects after one month with the usual treatment. The level of significance was assessed using Student’s t-test. All the subjects in this study had normal liver function tests and they did not suffer from iron overload diseases or any malabsorption of iron syndrome. Result: At baseline, serum Fe was significantly high in TB patients whereas serum TIBC was significantly decreased. After one month’s additional anti-TB (A-TB) drug treatment serum iron had increased but not significantly (p = 0.15) and serum TIBC had increased significantly (p = 0.04). Statistical computation of the ratio of serum Fe and serum TIBC in TB patients had shown to be as high as 0.63, and more than that. Conclusion: From statistical computation, it might be conferred that serum Fe more than 149 µg/dL and the ratio of serum Fe to serum TIBC more than 0.63 (which is more important) in preliminary survey detecting TB patients would shortlist the TB suspects deserving confirmatory test for TB diagnosis.